Balancing the needs of energy security, economic growth, and climate sustainability in ASEAN - Rika Safrina (Asian Development Bank Institute (ADBI), 2024)
This paper provides an integrative review of the energy landscape and cross-sectoral energy-related policies in the ASEAN Member States (AMSs) in balancing the needs of energy security, economic growth, and climate sustainability. To achieve this broad objective, the paper aims to investigate the changing structure of the economy by comparing it with the changing trends of energy sources in ASEAN. The analysis will use the historical data from 2005 to 2020 and the projection data from 2021 to 2050 from the 7th ASEAN Energy Outlook. This will reveal insights into whether, and if so how, net-zero emissions will be realized in ASEAN by or around the middle of the century. Given the important role of governments, we argue that a comprehensive review of national energy policies stated in official documents within the region is also essential to investigate the capability of AMSs to accelerate energy transition while securing energy supply. These official publications represent the voice of regime actors. Providing a novel contribution to the research, the second aim of the paper is to assess national policies in ASEAN related to energy transition away from coal, using horizontal integrated policy analysis. This will exhibit the ASEAN policymakers' perspective on how to accelerate energy transition while securing economic structural transformation. Structural transformation and the energy trilemma are the theoretical frameworks that motivate this study. It was found that coal will still be an important fuel in the ASEAN energy mix by 2050, making it challenging for the region to entirely phase out coal and achieve the decarbonization target. The region could stabilize its baseload renewable energy, such as hydro, geothermal, and bioenergy, while increasing its variable renewables intake through enhancing grid infrastructure, interconnection, and rural off-grid systems. A collaborative approach among cross-sectoral policymakers and support from the international community, especially in financing climate change mitigation, will be crucial for the region to balance its energy security, economic growth, and environmental sustainability.
Keywords: Q48; 330; structural transformation; energy trilemma; energy security; economic growth; climate sustainability